2020
DOI: 10.3390/cells9020472
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Cycle Checkpoint System MAST(L)-ENSA/ARPP19-PP2A is Targeted by cAMP/PKA and cGMP/PKG in Anucleate Human Platelets

Abstract: The cell cycle is controlled by microtubule-associated serine/threonine kinase-like (MASTL), which phosphorylates the cAMP-regulated phosphoproteins 19 (ARPP19) at S62 and 19e/α-endosulfine (ENSA) at S67and converts them into protein phosphatase 2A (PP2A) inhibitors. Based on initial proteomic data, we hypothesized that the MASTL-ENSA/ARPP19-PP2A pathway, unknown until now in platelets, is regulated and functional in these anucleate cells. We detected ENSA, ARPP19 and various PP2A subunits (including seven dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 91 publications
(122 reference statements)
3
36
0
Order By: Relevance
“…Citrated blood was supplemented with 2 mM EGTA and centrifuged for 10 min at 200× g. The resulting PRP was diluted with CGS buffer (120 mM NaCl, 12.9 mM trisodium citrate dihydrate, 30 mM d-glucose, pH 6.5) at a ratio of 1:1. For leukocyte depletion, the PRP was centrifuged for 10 min at 69× g. The resulting supernatant was subsequent centrifuged for 10 min at 400× g. The resulting pellet was resuspended in CGS buffer and again centrifuged for 10 min at 400× g. The platelets were resuspended in 1× PBS for flow cytometry [56].…”
Section: Isolation Of Pre-activated and Resting Platelets And Preparamentioning
confidence: 99%
“…Citrated blood was supplemented with 2 mM EGTA and centrifuged for 10 min at 200× g. The resulting PRP was diluted with CGS buffer (120 mM NaCl, 12.9 mM trisodium citrate dihydrate, 30 mM d-glucose, pH 6.5) at a ratio of 1:1. For leukocyte depletion, the PRP was centrifuged for 10 min at 69× g. The resulting supernatant was subsequent centrifuged for 10 min at 400× g. The resulting pellet was resuspended in CGS buffer and again centrifuged for 10 min at 400× g. The platelets were resuspended in 1× PBS for flow cytometry [56].…”
Section: Isolation Of Pre-activated and Resting Platelets And Preparamentioning
confidence: 99%
“…The activation of the cAMP/PKA pathway generally leads to the suppression of the MAPK pathway. 13 - 17 And the phosphorylation of ERK1/2 is in line with the activation of the MAPK pathway. In our experiments, it was observed that the phosphorylation level of ERK1/2 was obviously decreased in the HGC-27 control cells after treatment of ISO, meanwhile the phosphorylation level of ERK1/2 was retained in the CRY1o cells ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 79%
“… 9 - 12 The activation of the cAMP/PKA pathway generally inhibits the MAPK pathway, leading to inhibition of cell growth and proliferation. 13 - 17 Nevertheless, the levels of intracellular cAMP was altered by changes in β-adrenergic receptors, and then cell growth and differentiation were affected. 18 The β2-adrenergic antagonists was reported to suppress invasion and proliferation in pancreatic cancer cell by inhibiting cAMP/PKA pathway, which could regulate activation of the MAPK pathway.…”
Section: Introductionmentioning
confidence: 99%
“…A bioinformatical tool analyzer showed that MASTL could be stimulated by many TFs, such as SPI1 and KLF5 in stomach tissues [39] . In the other hand, MASTL could activate downstream signal pathway, such as AKT/mTOR and Wnt/b-catenin oncogenic kinase signaling [13] , the PKA, MAPK and PI3K/Akt signaling in human platelets [40] . PP1 regulatory subunit 3B (PPP1R3B) was found as a cell cycle regulator by governing MASTL dephosphorylation [41] .…”
Section: Discussionmentioning
confidence: 99%